1988
DOI: 10.1210/edrv-9-4-450
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autoantibodies in the Pathogenesis and Association of Endocrine Autoimmune Disorders*

Abstract: This review has focused on the nature and significance of aAB detected in the serum of patients with EAD. Although many antibodies are characteristically detected in the serum of patients with such disorders, only a few are of known pathogenic significance. Antibodies that react with soluble cytoplasmic antigens are not expected to be harmful. On the other hand, membrane or cell surface-directed antibodies are likely to be damaging, either by lysis of the cell membrane, or by reaction with hormone or other sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 129 publications
0
32
0
4
Order By: Relevance
“…In addition, other endocrine cells, such as pituitary cells and adrenal chromaffin cells, are known to have GAD, but are not always confined to GAD65 [37]. Furthermore, it was reported that autoantibodies to a 64 kDa protein isolated from the human thyroid and retroorbital tissue were identified in the sera of patients with thyroid-associated ophthalmopathy [38] and the same autoantibodies cross-reacted with a 64 kDa antigen expressed on the surface of human pancreas cell membranes [39]. But it is not yet clear whether the thyroid 64 kDa protein is similar to the 64 kDa islet autoantigen (GAD65) [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other endocrine cells, such as pituitary cells and adrenal chromaffin cells, are known to have GAD, but are not always confined to GAD65 [37]. Furthermore, it was reported that autoantibodies to a 64 kDa protein isolated from the human thyroid and retroorbital tissue were identified in the sera of patients with thyroid-associated ophthalmopathy [38] and the same autoantibodies cross-reacted with a 64 kDa antigen expressed on the surface of human pancreas cell membranes [39]. But it is not yet clear whether the thyroid 64 kDa protein is similar to the 64 kDa islet autoantigen (GAD65) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that autoantibodies to a 64 kDa protein isolated from the human thyroid and retroorbital tissue were identified in the sera of patients with thyroid-associated ophthalmopathy [38] and the same autoantibodies cross-reacted with a 64 kDa antigen expressed on the surface of human pancreas cell membranes [39]. But it is not yet clear whether the thyroid 64 kDa protein is similar to the 64 kDa islet autoantigen (GAD65) [39]. In any event, it is intriguing that the common 64 kDa autoantigen is present on both islet fl-cells and thyroid follicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnozuojant šią ligą, paciento serume randama antikūnų prieš fermentą -skydliaukės peroksidazę (mikrosominiai antikūnai), skydliaukės folikulų koloidą -tiroglobuliną (tiroglobulino antikūnai) ir prieš skydliaukę stimuliuojamąjį hormoną (angl. thyroid-stimulating hormone -TSH) receptorius (TSH receptorių antikūnai) (1). Sergant autoimunine skydliaukės liga, pačioje skydliaukėje sekretuojami skydliaukės autoantikūnai.…”
Section: įVadasunclassified
“…The greater use of drugs for hypothyroidism, adrenocortical hypofunction, pernicious anemia, and rheumatoid arthritis by diabetic individuals (particularly individuals with type 1 diabetes) than by control subjects undoubtedly reflects the frequent occurrence of type 1 diabetes with autoimmune disorders (21,22).…”
Section: Medication Use and Costs In Diabetesmentioning
confidence: 99%